Computational fluid dynamics modeling of a discrete feed atomic layer deposition reactor: Application to reactor design and operation - Tom, Matthew; Wang, Henrik; Ou, Feiyang; Yun, Sungil; Orkoulas, Gerassimos; Christofides, Panagiotis D. (Computers & chemical engineering, 2023)
Novel transistor fabrication methods such as area-selective atomic layer deposition (AS-ALD) are crucial to improving nanopatterning, which is essential for facilitating transistor stacking in semiconducting wafers. However, transistor surfaces are subjected to nonuniformities during the initial AS-ALD adsorption reactions that are attributed to steric hindrance effects. To minimize the role of steric hindrance generated by an oversaturation of reagent on the substrate surface, a discrete feed method is proposed for an ALD reactor configuration where reagent is introduced in short pulses through a perpendicular delivery system. An optimal reactor configuration is developed by modifying the inlet geometries of the reactor to ensure ideal fluid dynamics conditions (e.g., minimal vortices, radial flow distribution) are achieved. Detailed computational fluid dynamics simulations demonstrate the performance of the new reactor configuration and operational strategy. •Computational fluid dynamics modeling of a discrete feed ALD reactor.•Optimization of reagent delivery system.•Minimization of steric hindrance effects.•Reactor optimal operation is determined.